Influence of α-Cyclodextrin on gold extraction to reduce occupational accidents and environmental impacts - Zegarra Ruiz, Luis Anthony (2022)
The gold extraction method with α-cyclodextrin in the mineral sample was applied to the study sample, then the incidence in the reduction of occupational accidents and negative environmental impacts was determined and the problems were raised. α-cyclodextrin in the extraction of gold in ore influences the reduction of occupational accidents and negative environmental impacts? To what extent does the realization of the hazard identification and risk assessment matrix, and calculate the percentage of occupational risk of the method of gold extraction with α-cyclodextrin can lead to occupational accidents? and To what extent can carrying out the matrix for the identification of aspects and evaluation of environmental impacts, and calculating the percentage of the environmental risk index of the gold extraction method with α-cyclodextrin, can generate environmental impacts?. The method was based on scientific articles Sousa et al. (2018) and Liu et al. (2013), that was modified for its application in the study sample, the results obtained from the gold extraction showed a maximum recovery of 3.9% of gold, with an environmental risk index and average occupational risk index of 2.